Impact of Covid-19 in Bangladesh Stock Market - Haque, Sunjida; Chowdhury, Tanbir Ahmed (Asian Finance & Banking Review, 2020)
The world's big economies are roiled and going under a devastating threat amid the impact of the COVID-19 pandemic. No country will be safe as this virus will eventually outbreak everywhere, regardless of how countries prepare to avoid it. The economic ramification as well as the stock market crisis will be uncertain due to the extended suspension of economic activities in almost every country. No wonder, the clattered stock markets of Bangladesh which have already got the adjective of “the worst stock market in the world” because of inefficient and irrational fluctuations in previous years will experience a colossal crisis due to the pandemic. The article provides an investigation on comparable analysis of the impact on stock markets of Bangladesh, Dhaka stock exchange, and Chittagong stock exchange, before and after the pandemic situation with current market data. We also examine the potential consequence of policy interventions to the market and the investors during a pandemic.